Ghost Imaging at the Free-Electron Laser FLASH - Kim, Young Yong; Gelisio, Luca; Mercurio, Giuseppe; Dziarzhytski, Siarhei; Beye, Martin; Bocklage, Lars; Classen, Anton; David, Christian; Gorobtsov, Oleg Yu; Khubbutdinov, Ruslan; Lazarev, Sergey; Mukharamova, Nastasia; et al. (Optics InfoBase Conference Papers, 2021)
A classical ghost imaging experiment performed at the free-electron laser FLASH is presented. The possibility of image formation, a double bar in our case, in the beam that has never interacted with the sample is demonstrated.
CRIS-Team Scopus Importer:2023-03-27